Healthy from the Village (Village Communities Health Empowerment Strategy Based on Capacity Development) - Saputra Adiwijaya (Indonesian Association for Public Administration (IAPA), 2018)
The village as the smallest government in the formal scope of the unitary state of the Republic of Indonesia is currently an interesting focus to study, especially since the Village Fund Allocation (ADD) was rolled out by the central government of 1 billion per village, making the village actively build in all aspects. One of the focus in the development of the village communities is the health sector, as this area is considered as one of the main pillars in the effort to build a nation. Empowerment in the health sector is absolutely necessary as an alternative in adjusting the varying conditions of villages in Indonesia, in other parts the empowerment program also refers to adjustments from the world programs contained in the SDG's (Sustainable Development Goals). This paper tries to give perspective about the urgency of health empowerment for village communities based on capacity building as one of the ideas offered in preparing technical policies for the health sector in the village. In another section details the empowerment program for village communities which are based on the capacity development aims to facilitate the passage of the program and must be adjusted to the potential of the existing village.